2019
DOI: 10.32615/ps.2019.111
|View full text |Cite
|
Sign up to set email alerts
|

Relative tolerance of photosystem II in spike, leaf, and stem of bread and durum wheat under desiccation

Abstract: In dryland regions, soil moisture stress often leads to desiccation and causes injury to photosynthetic machinery. Recently, chlorophyll fluorescence (ChlF)-based assessment of photosynthetic efficiency under drought stress is gaining attention due to advances in instrument development and methodology optimisation. Our study was designed to explore the use of spike photosynthetic efficiency as a trait to differentiate drought responses in wheat. Bread and durum wheat were assessed for spike, stem, and leaf tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…The correlation analysis also revealed that PN positively correlated with Car and Chl (Table 1). Previous research observed that a suitable concentration of La improves the contents of the photosynthetic pigments, accelerates the absorption of the light energy, and then promotes the efficiency of photosynthesis (Rathore and Jasrai 2013, Ma et al 2017, Rane et al 2019. Two explanations may account for the effect of La on the photosynthetic pigments.…”
Section: Discussionmentioning
confidence: 98%
“…The correlation analysis also revealed that PN positively correlated with Car and Chl (Table 1). Previous research observed that a suitable concentration of La improves the contents of the photosynthetic pigments, accelerates the absorption of the light energy, and then promotes the efficiency of photosynthesis (Rathore and Jasrai 2013, Ma et al 2017, Rane et al 2019. Two explanations may account for the effect of La on the photosynthetic pigments.…”
Section: Discussionmentioning
confidence: 98%
“…Kim et al [ 64 ] analyzed F 0 , Fm, and Fv values to determine photosynthetic efficiency according to chlorophyll fluorescence in rice and drought tolerant mutant showed higher Fv, Fm, Fm/F 0 and Fv/Fm than wild types. Chlorophyll fluorescence has also been quantified in a specific plant part, including the spike, leaf, and stem [ 49 ] or in the top-view and side-view of a plant [ 36 , 50 ]. The optimal photosystem II (PS II) efficiency and parameters for the HTP experimental procedure must be identified [ 51 ].…”
Section: Htp Methodsmentioning
confidence: 99%
“…Under no stress condition, the proline level was 2.17 ±0. 35 Higher expression of GmWRKY transcription factor FAD3A overexpressing plants under drought and salinity stress Differential tolerance to abiotic stress was achieved in Arabidopsis when transformed with GmWRKY transcription factor (Zhou et al 2008). This prompted us to study the expression of WRKY transcription factor in FAD3A overexpressing plants.…”
Section: Increase In Proline Level In Fad3a Overexpressing Plants Und...mentioning
confidence: 99%
“…Leaf chlorophyll content is considered to be a good indicator of photosynthetic capability in terms of Photosystem-II (PS-II, Fv/Fm) e ciency. Maximum quantum yield (QYmax) in terms of Fv/Fm value, which indicates photochemical e ciency varies with severity of drought and decreased drastically during prolonged drought stress(Zivcak et al 2008;Rane et al 2019;). Kumar et al (2017) reported that photosynthetic e ciency in soybean was closely associated with canopy greenness re ected by higher chlorophyll content.…”
mentioning
confidence: 99%